A novel ternary deep eutectic solvent for efficient recovery of critical metals from spent lithium-ion batteries under mild conditions. Issue 6 (December 2022) - Liao, Yanshun; Gong, Shanshan; Wang, Guange; Wu, Tong; Meng, Xianglei; Huang, Qing; Su, Yuefeng; Wu, Feng; Kelly, Ryan M.
Abstract: In terms of environmental pollution and the shortage of resources, an efficient recovery of valuable metals in spent lithium-ion batteries (LIBs) is currently the most promising measure to achieve green sustainability of cathode materials. In this study, an choline chloride (ChCl)/ benzenesulfonic acid (BSA)/ ethanol ternary deep eutectic solvent (e.g., ChCl:BSA:Ethanol = 1:1:2 in molar ratio) was designed and applied to efficiently leach lithium (Li) and cobalt (Co) from spent LIBs under mild conditions. The experimental results show that the leaching efficiencies of Li and Co can reach 99% and 98%, respectively, under the optimal conditions: (i) a reaction temperature of 90 °C, (ii) a Solid/Liquid ratio of 20 g L −1, (iii) ChCl:BSA:Ethanol with a molar ratio of 1:1:2 and (iv) a reaction time of 2 h. The kinetics of the leaching process shows that the leaching is controlled by a surface chemical reaction. Furthermore, the Co 2+ in the leachate can be directly converted into Co3 O4 via precipitation of H2 C2 O4 and NaOH and calcination. The recovered high-value product Co3 O4 can regenerate the LiCoO2 cathode material. This study provides a new method for the green recovery of spent LIB cathode materials with high efficiency and low energy consumption. Graphical Abstract: ga1 Highlights: A choline chloride/benzene sulfonic acid/ethanol ternary DES for spent lithium-ion batteries recycling was synthesized for the first time. Greater than 99% of Li and 98% of Co can be leached under mild conditions. Regenerated cathode exhibits comparable performance to the commercially synthesized cathode. A high-efficiency and closed-loop short-range spent Li2 CoO2 regeneration route was constructed.